Productivity analysis of crops grown in saline environment: presentation of the major research lines - Katerji N. (Mediterranean crop responses to water and soil salinity: Eco-physiological and agronomic analyses, 2002)
The various approaches mentioned in the literature are investigated to characterize crop responses to saline stress. In each case, the steps undertaken are presented and examples of the results obtained underlined. In addition, the presentation is accompanied by a critical analysis showing the advantages and limitations of each approach. In conclusion, we evoke arguments pleading for an eco-physiological approach associating a description of plant water behaviour in a saline environment with yield related to observations.